2005
DOI: 10.1152/japplphysiol.01071.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaginal distension on blood flow and hypoxia of urogenital organs of the female rat

Abstract: Vaginal delivery of children causes traumatic injury to tissues of the pelvic floor and is correlated with stress urinary incontinence; however, the exact mechanism of organ and tissue injury leading to incontinence development is unknown. The purpose of this project was to test the hypothesis that vaginal distension results in decreased blood flow to, and hypoxia of, the urogenital organs responsible for continence, which would suggest an ischemic and/or reperfusion mechanism of injury. Thirteen female rats u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
62
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 41 publications
4
62
4
Order By: Relevance
“…The biomechanical changes observed in our model for acute SUI may stem from functional, structural, neural, or vascular alterations that result from VD (1,5,9,13). Previous in vivo investigations using a similar model showed that simulated birth trauma produces lower bladder leak-point pressures compared with healthy controls (5).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The biomechanical changes observed in our model for acute SUI may stem from functional, structural, neural, or vascular alterations that result from VD (1,5,9,13). Previous in vivo investigations using a similar model showed that simulated birth trauma produces lower bladder leak-point pressures compared with healthy controls (5).…”
Section: Discussionmentioning
confidence: 85%
“…The observed biomechanical changes may also stem from damaged lower urinary tract vasculature. Using a rat model similar to the one used in the current work, Damaser et al (9) studied blood flow to three major pelvic organs: bladder, vagina, and the urethra. The bladder and the urethra experienced periods of hypoxia during VD, which can greatly affect the urothelium and neuromuscular components of this tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In that position, the balloon compressed the organs of the pelvic area (pelvic vagina, pelvic urethra, rectum, pelvic floor muscles, and its vessels and nerves) against the pelvic bone and distended the perineal genitourinary tract (distal region of the vagina and urethra and the vessels and nerves related to them). Thus, the VD model in rats produces direct mechanical damage to the pelvic urethra and distal genitourinary tract, which may explain the resultant disorganization and thinness of the EUS (4, 39) and the physiological impairment observed after VD, such as hypoxia of the genitourinary organs, indicating a reduction in blood flow (9), abolished EUS activity (21), decreased leak point pressure, and/or urine leakage with effort, suggesting urethral closure incompetence (26, …”
Section: Discussionmentioning
confidence: 99%
“…A prolonged parturition can be modeled with VD of greater duration than the duration of parturition in intact rats (19,34). Using the VD model, investigators have demonstrated bladder, urethral, and vaginal hypoxia (9), anatomic and functional damage to the EUS and its innervation (4,21), and decreases in urethral resistance (26). Whether these VDinduced structural and functional changes are sufficient to cause signs of voiding dysfunction in awake animals is unknown.…”
mentioning
confidence: 99%
“…This finding was echoed by Cannon et al (6), who showed that increased duration of vaginal distention and multiple vaginal deliveries also decreased leak point pressures and increased anatomical injury. It may be that the distention causes ischemia to the urethra or that there is reperfusion injury after the vaginal distention has resolved (8). A similar mechanism of injury may be operative in the connective tissues of the vaginal wall.…”
Section: Discussionmentioning
confidence: 99%